Analisis Studi Kelayakan UMKM Kaysha Fire Chicken - Putri Nazli; Annisa Prastiwi (Institut Teknologi dan Bisnis Semarang, 2025)
A business feasibility study is a series of assessments that can be used to measure the feasibility of an investment or business proposal. Both new businesses and development of existing businesses. Kaysha Fire CHIcken, which has been operating for more than 2 years in Tanjung Mulia Medan, plans to expand its business by opening a new branch in Marelan as one of the steps to make the business better known to the people of North Sumatra. This research has used 7 main aspects that are commonly used in analyzing business feasibility and obtained the results that all these aspects show the business development plan seen from legal, market and marketing, financial, technical and operational, management and organizational, economic and social aspects as well as The environmental impact shows good results and is feasible to carry out, namely by opening this new branch. The research used is qualitative and quantitative research using field observation data collection techniques and documents from documents that have occurred in the main business, especially regarding financial reports. The selection of branch loci is also based on decisions outlined in technical and operational aspects.